2015
DOI: 10.1016/j.chiabu.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Determining women's sexual self-schemas through advanced computerized text analysis

Abstract: The meaning extraction method (MEM), an advanced computerized text analysis technique, was used to analyze women’s sexual self-schemas. Participants (n = 239) completed open-ended essays about their personal feelings associated with sex and sexuality. These essays were analyzed using the MEM, a procedure designed to extract common themes from natural language. Using the MEM procedure, we extracted seven unique themes germane to sexual self-schemas: family and development, virginity, abuse, relationship, sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
40
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 34 publications
8
40
1
Order By: Relevance
“…Author Manuscript Author Manuscript attraction schema was previously found to differ between women with and without a history of CSA, with abused women showing a greater prominence of this schema than non-abused women (Stanton et al, 2015). Two notable patterns of sexual behavior have been observed in women with a history of CSA: hypersexuality and hyposexuality (Rellini, 2008).…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…Author Manuscript Author Manuscript attraction schema was previously found to differ between women with and without a history of CSA, with abused women showing a greater prominence of this schema than non-abused women (Stanton et al, 2015). Two notable patterns of sexual behavior have been observed in women with a history of CSA: hypersexuality and hyposexuality (Rellini, 2008).…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…Hypersexuality has been posited to be related to high impulsivity. It is possible that some of the abused women in the current study had a history of hypersexuality, which might have been expressed through a higher use of the attraction schema in their pre-treatment essays.As treatment helped women to process their abuse history, their tendency towards impulsivity and hypersexuality may have decreased, which was then reflected through a reduction in the attraction schema.Previous research has shown that non-abused women write about the relationship schema, which focuses on intimacy and connection with a romantic partner, more than abused women (Stanton et al, 2015); therefore we predicted that abused women would write about this schema more over time. Consistent with our hypothesis, the relationship schema showed a significant increase in prominence between the pre-treatment and post-treatment assessments (Figure 1 Panel D), yet this increase was not maintained over time in the followup sessions.…”
mentioning
confidence: 92%
See 3 more Smart Citations